Incidence rate and geographic distribution of congenital hypothyroidism in the southwest of Iran (Kohgiluyeh and Boyer Ahmad province) based on geographic information system since 2011-2020 - Mohammad Amin Ghatee; Leila Manzouri; Maryam Kheiri; Mohamad Parad (BMC, 2024)
Abstract Background Congenital hypothyroidism (CH) is one of the most prevalent preventable cause of mental retardation and intellectual disability in newborns. Genetic and environmental factors have been related to congenital hypothyroidism. Hence, this study was conducted to illustrate the incidence and spatial distribution of the CH using the dataset from the national newborn CH screening information system during 2011-2020in counties affiliated to the Kohgiluyeh and Boyer Ahmad University of Medical Sciences. Methods This was a cross-sectional study. All newborns that were screened for CH in 3-5 days of age in the health centers of Yasuj University of Medical Sciences were enrolled the study since 2011-2020. Meteorological data including information on temperature, humidity, precipitation in a 10-year period (2011-2020) was taken from the Meteorological Organization. The required information layers include slope, slope direction, height, vegetation and political divisions of the province, were purchased from the organizations that made the layers. The data related to the incidence of congenital hypothyroidism was collected from the 10-year reports of the provincial health center. Addresses of patients were transferred to Arc GIS 10.5 software and entered in urban and rural point's layer to prepare and draw disease distribution maps in the province's newborns. The influence of geographical factors on the occurrence of disease was done by SPSS 23 software using multivariate binary logistic regression. P-value < 0.05 was assumed as significant level. Results Out of 142,674 screened newborns for CH, 827 had positive screening, including 441 boys (53.3%) and 386 girls (46.7%). Total incidence per 1000 live birth was 5.79. Based on multivariate logistic regression, slope (sig = 0.0001, Exp(B) = 0.91, CI95% Exp(B) = 0.87-0.95), thin forest (sig = 0.001, Exp(B) = 0.2, CI95% Exp(B) = 0.07-0.53), water area (sig = 0.0001, Exp(B) = 8.91, CI95% Exp(B) = 3.35-23.69), were predicting factors of CH. Conclusion Given that, the incidence of CH in the Kohgiluyeh and Boyar Ahmad province is higher than the average of country (Iran), and the geographical factors of land slope and type of vegetation were related to it that cannot be changed, it is very important to carry out necessary nutritional interventions during pregnancy to prevent newborns from contracting this disease.